Pengaruh Kepercayaan Konsumen Dan Kualitas Produk Terhadap Keputusan Pembelian Pada PT Batam Bangun Prahtama - Riny Susanti; Triana Ananda Rustam (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2022)
In today's era with increasingly fierce competition, consumer trust and product quality are considered quite important in order to running a company. These two points are considered to be able to influence consumer in purchasing decisions. PT Batam Bangun Prahtama or known as BBP are a distributor of building material company in Batam. In order to overcome this competition, PT BBP has demanded to further improve and maintain Purchaser trust and item caliber, so that purchases decisions can be affected. This study/research proposed on focus the impact from purchaser trust (X1) and item caliber (X2), for purchasing decisions (Y) toward PT Batam Bangun Prahtama.. The metode of this study/research are quantitative, collecting data by distributing questionnaires containing statements by using the google form. The population in this study/research in total amount of 249 customers, this study/research sample used simple random sampling with a sample of 153 customers. The researcher uses SPSS Version 25 to process data. The results of this study indicate that purchaser trust and item caliber have a significant and positive effect on purchasing decisions. Simultaneously or jointly, purchaser trust and item caliber have a partial and significant impact on purchasing decisions at PT Batam Bangun Prahtama